2021
DOI: 10.3389/fimmu.2021.697298
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors With or Without Bone-Targeted Therapy in NSCLC Patients With Bone Metastases and Prognostic Significance of Neutrophil-to-Lymphocyte Ratio

Abstract: IntroductionBone metastases (BMs) are a negative prognostic factor in patients with non-small cell lung cancer (NSCLC). Although immune-checkpoint inhibitors (ICIs) have dramatically changed the therapeutic landscape of NSCLC, little information is available on BMs from NSCLC treated with ICIs alone or in association with bone-targeted therapy (BTT) such as zoledronate or denosumab.MethodsFrom 2014 to 2020, 111 of the 142 patients with BMs secondary to NSCLC extrapolated from the prospective multicenter Italia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Our study results were partly supported by previous data from Bongiovanni et al. ( 15 ), whose work indicated a better mPFS (15.9 months; 95%CI, 5.1–not estimable) of patients receiving denosumab (n = 6) than those treated with ICIs alone or with ZA ( p = 0.068).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study results were partly supported by previous data from Bongiovanni et al. ( 15 ), whose work indicated a better mPFS (15.9 months; 95%CI, 5.1–not estimable) of patients receiving denosumab (n = 6) than those treated with ICIs alone or with ZA ( p = 0.068).…”
Section: Discussionsupporting
confidence: 90%
“…However, treatment with ZA was confounded in the study arm, so the synergistic effect of denosumab and immunotherapy could not be accurately assessed. Furthermore, it is possible that the additional prolongation of survival in the experimental group shown by the study results was due to the survival benefit of BTT by reducing SREs rather than synergy with immunotherapy ( 15 ). A summary of published data on the combination of denosumab and ICIs is demonstrated in Table 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, dNLR has been used as a novel biomarker to predict response to immunotherapy in various cancers including NSCLC, melanoma and head and neck cancers ( 39 , 40 ). It has been shown that a high pre-treatment dNLR (indicating a high inflammatory state) is associated with poor OS and PFS in a variety of cancers ( 37 , 39 42 ). For instance, Bongiovanni et al, observed a positive association between OS and a NLR ≤ 5 ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective analysis of data on 111 NSCLC patients extrapolated from the prospective Italian register of bone metastasis (BMDB) (from 2014 to 2020) confirmed, despite a limited number of patients treated with ICIs (n = 46), that the use of BTT (30 patients) with ICI monotherapy increases OS from 15.8 months to 21.8 months [ 38 ]. Regarding the response on bone evaluated with the MD Anderson criteria, 43.5% of patients obtained a partial response following ICIs plus BTT, while the same response was obtained in only 16.7% of patients treated with ICIs alone.…”
Section: Bone Metastasis In Nsclc Treated With Immune Checkpoint Inhi...mentioning
confidence: 99%